Gambaran Motivasi Donor Darah pada Pendonor Sukarela di Unit Donor Darah PMI Kabupaten Sleman Tahun 2021 - Nur'Aini Purnamaningsih; Rizky Novianingsih; Ratna Prahesti (Poltekkes Kemenkes Padang, 2022)
Blood donation is an activity to donate blood for blood transfusion purposes. A person who is a donor needs to know the motivation of blood donors to become a sustainable voluntary donor. This study aims to determine the motivation of blood donors to voluntary donors in the Blood Donor Unit PMI Sleman in 2021. This study is a descriptive study with a sample of 100 voluntary donors. The sampling technique is quota sampling by analyzing the frequency distribution data and the percentage of each variable. The results showed that the characteristics of voluntary blood donors at the PMI Blood Donor Unit in Sleman Regency in 2021 were the majority of the late adolescent age group (17-25 years) as many as 45 people (45%), male sex 60 people (60%), education high level (academic/college) 73 people (73%), and not working (student) 36 people (36%). The most dominant motivation for blood donation for voluntary donors at the PMI Blood Donor Unit in Sleman Regency in 2021 is because they want to help 99 people (99%). The motivation of donors at UDD PMI in Sleman Regency is quite good. For this reason, it is recommended to increase socialization to the community regarding the importance of routinely donating blood.